Introduction of Open E-Learning System as a Factor of Regional Development - Bystrova, Tatiana Yuryevna; Larionova, Viola Anatoylevna; Osborne, Michael; Platonov, Anatoly Mikhaylovich (Economy of Regions, 2015)
The article analyses the economic and socio-cultural premises for introducing the open e-learning in the Ural region, as well as the potential economic effect of this type of educational activity. The article strives to prove a regular pattern of the universities’ transition to e-learning, also in connection with the changes of the educational paradigm and the nature of the educational system management. The hypothesis of the paper is connected with bringing the economic dimension to a humanitarian concept of e-learning, which becomes more and more widespread. The methodology of the article is based on the recognition of the fact that the macroeconomic processes in the information society and the processes occurring in a particular industry - higher education - are of isomorphic nature. On the basis of the analysis of global experience and basic theoretical approaches to e-learning, including the Lifelong Learning concept, the authors make a conclusion of the progressive growth of interest in different countries and regions. The e-learning is treated primarily as a tool to improve quality and efficiency of the educational process. The accuracy of understanding functions and peculiarities of e-learning allows one to determine a positive economic effect of its application for the university, the region, and the employers. The article shows organisational mechanisms and financial model of implementing e-learning in the Ural Federal University. The description is made of the cost options for open-type e-learning course development, investment parameters for their establishment, as well as costs of implementing educational programmes with the application of e-learning. The analysis of the activities of Ural Federal University on implementing e-learning gives the opportunity to further imagine the effect from the introduction of e-learning in other universities in the region. The results of the research may be applied in the institutions of secondary and higher education in the decision concerning the volume and form of the e-learning system.